Pedagogical affect, student interest, and learning performance - Abrantes, José Luís (2016)
Using a sample of more than 1000 students, this study reveals that students’ perceived learning depends directly on their interest, pedagogical affect, and their learning performance and indirectly on the student–instructor interaction, the instructor's responsiveness, course organization, the instructor's likeability/concern, and the student's learning performance. Likeability/concern indirectly affects student interest by influencing learning performance. The results yield recommendations for schools, department heads, and university administrators.